Loss of zinc transporters ZIP1 and ZIP3 augments platelet reactivity in response to thrombin and accelerates thrombus formation in vivo - Elgheznawy, Amro; Öftering, Patricia; Englert, Maximilian; Mott, Kristina; Kaiser, Friederike; Kusch, Charly; Gbureck, Uwe; Bösl, Michael R.; Schulze, Harald; Nieswandt, Bernhard; Vögtle, Timo; Hermanns, Heike M. (Frontiers in Immunology, 2023)
Zinc (Zn2+) is considered as important mediator of immune cell function, thrombosis and haemostasis. However, our understanding of the transport mechanisms that regulate Zn2+ homeostasis in platelets is limited. Zn2+ transporters, ZIPs and ZnTs, are widely expressed in eukaryotic cells. Using mice globally lacking ZIP1 and ZIP3 (ZIP1/3 DKO), our aim was to explore the potential role of these Zn2+ transporters in maintaining platelet Zn2+ homeostasis and in the regulation of platelet function. While ICP-MS measurements indicated unaltered overall Zn2+ concentrations in platelets of ZIP1/3 DKO mice, we observed a significantly increased content of FluoZin3-stainable free Zn2+, which, however, appears to be released less efficiently upon thrombin-stimulated platelet activation. On the functional level, ZIP1/3 DKO platelets exhibited a hyperactive response towards threshold concentrations of G protein-coupled receptor (GPCR) agonists, while immunoreceptor tyrosine-based activation (ITAM)-coupled receptor agonist signalling were unaffected. This resulted in enhanced platelet aggregation towards thrombin, bigger thrombus volume under flow ex vivo and faster in vivo thrombus formation in ZIP1/3 DKO mice. Molecularly, augmented GPCR responses were accompanied by enhanced Ca2+ and PKC, CamKII and ERK1/2 signalling. The current study thereby identifies ZIP1 and ZIP3 as important regulators for the maintenance of platelet Zn2+ homeostasis and function.